Aplikasi Pembelajaran Latihan Dasar-Dasar Bola Basket 3 Dimensi Menggunakan Metode Multimedia Development Life Cycle Berbasis Android - Prajoko Prajoko; Winda Apriandari; Gusti Aldy Reynaldy (The Faculty of Science and Technology, 2019)
The world of basketball is one sport that can be considered a sport with very many enthusiasts, with manydiverse exercises sometimes the players are confused to understand the exercises that are so much varied,especially for beginners, it is expected that learning media can help beginners to understand the practice, atleast to understand the basics of basketball. Today's technology has penetrated into all aspects of human life,both technology as a work aid, technology as a means of socializing, educating, or technology forentertainment such as games. The development of technology also means the development of learningapplication, the development of learning application has an impact on education. The world of educationtoday has become more sophisticated in its implementation. Not only using whiteboards and chalk, buthaving switched to computers and projectors even through learning application a science can be delivered ina way that is more fun and interesting. Educators are even easier in sharing their knowledge with the help oftechnology. Multimedia Development Life Cycle Multimedia development so that it can be included inlearning must go through well-designed and coherent stages so that the multimedia products produced are ofgood quality and appropriate to be used in learning. This learning application produces material that canhelp beginner basketball players to learn basketball which is good and right